Mycophenolate mofetil therapy for severe immune thrombocytopenia. (6th August 2015) - Taylor, Alice; Neave, Lucy; Solanki, Shalini; Westwood, John Paul; Terrinonive, Ilaria; McGuckin, Siobhan; Kothari, Jaimal; Cooper, Nichola; Stasi, Roberto; Scully, Marie
Summary: Severe immune thrombocytopenia purpura (ITP) presents a clinical challenge. Second‐line treatment options are variable without a precise protocol. We present 46 severe ITP patients treated with mycophenolate mofetil (MMF), retrospectively identified from three London teaching hospitals. Data was collected on patient demographics, co‐morbidities and previous treatment strategies. Our key interest was whether there was a sustained response in platelet count to MMF. Patients included 27 males and 19 females whose ages ranged from 19 to 93 years old (median 52·5 years). Twenty‐nine had primary ITP and 17 had secondary ITP, a third of whom had viral‐associated disease. The standard dose of MMF was 1 g/day. Twenty‐four patients (52%) responded with 15 (33%) achieving a complete response. No active viral‐associated ITP patients demonstrated a response to MMF, although numbers were small ( n  = 4). We were not able to demonstrate a difference between responders and non‐responders based on gender, age, previous therapies or time since diagnosis of ITP. Three of four previously splenectomized patients responded, two achieving complete response. We conclude that MMF is a useful steroid‐sparing immunosuppressant to be considered in the second‐line or later treatment of ITP.